Public Sector Innovations and Economic Stability: A Literature Review - Muh Yamin Noch; Yaya Sonjaya; Entis Sutisna (Yayasan Vifada Cendikia Indonesia, 2023)
This literature review investigates the relationship between public sector innovations and economic stability, focusing on initiatives in public financial management, digital governance, and policy innovations. Utilizing a qualitative research design, it synthesizes insights from existing scholarly works to identify key innovations such as performance-based budgeting, accrual accounting, and e-government, which enhance efficiency, transparency, and accountability in governance. The findings reveal that these innovations significantly contribute to economic stability by optimizing resource allocation, reducing fiscal risks, and fostering sustainable growth. However, implementing such innovations faces challenges, including bureaucratic resistance, political constraints, and organizational inertia. Overcoming these obstacles requires proactive strategies such as capacity building, fostering collaboration, and incentivizing innovation within the public sector. The discussion emphasizes the importance of aligning innovation strategies with broader economic goals, leveraging evidence-based decision-making, and fostering public-private partnerships to enhance the effectiveness of innovations. The implications suggest that governments must adopt a strategic, coordinated approach to fully leverage public sector innovations for long-term economic stability and societal advancement, thereby ensuring resilience and prosperity.